Study on biosynthesis and recovering of S-adenosyl-L-methionine (SAM) from Saccharomyces strains - Hương, Lê Thị Mai; Toàn, Phạm Đức; Trọng, Lê Văn; Trâm, Nguyễn Thị Hoài; Hòa, Hoàng Đình (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 105-114, 2005